Physics of organic semiconductors - Brütting, Wolfgang, 1966-; Adachi, Chihaya, 1963- (Wiley-VCH,;, 2012)
"The field of organic electronics has seen a steady growth over the last 15 years. At the same time, our scientific understanding of how to achieve optimum device performance has grown, and this book gives an overview of our present-day knowledge of the physics behind organic semiconductor devices. Based on the very successful first edition, the editors have invited top scientists from the US, Japan, and Europe to include the developments from recent years, covering such fundamental issues as: growth and characterization of thin films of organic semiconductors, charge transport and photophysical properties of the materials as well as their electronic structure at interfaces, and analysis and modeling of devices like organic light-emitting diodes or organic lasers. The result is an overview of the field for both readers with basic knowledge and for an application-oriented audience. It thus bridges the gap between textbook knowledge largely based on crystalline molecular solids and those books focusing more on device applications."--Resumé vydavatele
Keywords: polovodiče; organické sloučeniny; organická elektronika; vodivé polymery; semiconductors; organic compounds; organic electronics; conducting polymers; kolektivní monografie; elektronické knihy; collective monographs; electronic books